2D Layered Materials for Memristive and Neuromorphic Applications. (11th December 2019) - Wang, Chen‐Yu; Wang, Cong; Meng, Fanhao; Wang, Pengfei; Wang, Shuang; Liang, Shi‐Jun; Miao, Feng
Abstract: With many fantastic properties, memristive devices are a top candidate for next‐generation memory and neuromorphic computing chips. Significant research progress has been made in improving the performance of individual memristive devices and in demonstrating functional applications based on small‐scale memristive crossbar arrays. However, practical deployment of large‐scale traditional metal‐oxide‐based memristive crossbar arrays has been challenging due to several issues, such as high power consumption, poor device reliability, and low integration density. To solve these issues, new materials that exhibit superior properties are required. 2D layered materials exhibit many unique physical properties and show great promise in solving these challenges, further providing new opportunities to implement practical applications in neuromorphic computing. Recent research progress in 2D layered‐material‐based memristive device applications is reviewed. An overview of the progress in and challenges for the use of 2D layered materials to solve the issues of conventional memristive devices and to realize more complex functionalities in neuromorphic computing is provided. Additionally, an outlook of exploitation of the unique properties of 2D layered materials and van der Waals heterostructures for developing new types of memristive devices and artificial neural microcircuits is given. Abstract : The unique properties of 2D materials open up unprecedented opportunities for development of memristive and neuromorphic devices. Recent progress in 2D‐material‐based memristive and neuromorphic devices is reviewed, together with a thorough discussion on the challenges and opportunities in the future development of 2D‐based neuromorphic chips with low power consumption and multifunctionality.